Predictors of Health Promotion Behavior of female Students of Azad Islamic University, Kazerun Branch: Role of Social Support and Health Literacy - Soheyla Ziaee (Mashhad University of Medical Sciences, 2018)
Background and objective: Health promoting behaviors and life style at the young age is regarded as very important issues. The purpose of the present study is to investigate the relationship between social support and health literacy whit health promoting behaviors among female students in Islamic Azad University, in Kazerun, Iran. Methods: In this descriptive-analytic study, 200 female Azad University students were selected as the sample using random cluster sampling. The required data were collected using the Sarason's Social Support Questionnaire, Health Literacy Questionnaire devised by Montazeri et al., and Walker's Promoting Behaviors Questionnaire.  The data were analyzed using SPSS software (version 22), Pearson correlation coefficient and regression analysis. Results: Health promoting behaviors and health literacy scores in students were 74.32 and 76.68, respectively. The average for individuals in the students’ social support network was 3.8 ± 1.9 and the mean score of their satisfaction from their own social network was 4.9 ± 1.5. The results obtained from regression analysis showed that health literacy comprised 22.2% of health promoting behaviors while social support demonstrated 17.8% of these behaviors. Conclusion: Though health literacy and health promoting behaviors have been in a desirable condition for students, it seems necessary to carry out health education programs on the basis of the areas of health promoting behaviors and health literacy components as well as assisting students to improve social networking and to moderate their expectations with respect to this network. Paper Type: Research Article.